Long standing jump as the most appropriate method of evaluation of explosive strength of lower limbs - Mucha, D.; Görner, K.; Jurczak, A. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2012)
It is hard to imagine motive activities led according to the program which does not take into account gymnastics, athletics as well as sports team games requiring jump, strike, bounce etc. While doing all these exercises, some motions appear, which are directly connected with developing maximal strength. Everyone should monitor the level of fitness, which is changing with the lapse of time, situation or training. Strength, usually called dynamic force, is associated and strongly connected not only with sport but also with physical reaction and physical education. The aim of the undertaken studies was an attempt to solve the problem of finding a proper test of diagnosing strength, Sargent`s vertical jump or a long jump. The research was carried out among 121 of schoolgirls and 128 schoolboys of the junior high school. The participants of the tests were asked to make the attempt of the vertical jump as well as the long jump twice. The obtained data were analyzed by comparing the results of the mentioned tests with the help of the Pearson`s indicator. Mean value, the minimal and maximal, was also counted up and compared to the norms elaborated in the open for general use fitness tests. The review of the field tests with reference to both tests was also made. Research tools of the Polish and foreign authors were analyzed with regard to the strength diagnosis. Taking into account the Pearson`s modulus of correlation, it can be claimed that both tests can be used interchangeably. Analysis of the fitness tests used in Poland, Europe and in the whole world shows that in almost every research tool elaborated for the needs of accessing motor abilities, the test of strength can be found, although it does not always have to be a vertical jump or a long jump. However, the findings accomplished by the junior high school students analyzed on the basis of the norms enclosed in the Czech and Dutch Fitness Tests and the review of the field tests show that more reliable and easier to be carried out is the trial of a long jump.